Penyuluhan Hukum Tentang Pentingnya Pembelajaran Menjaga dan Memelihara Lingkungan Hidup di SD Negeri 7 Syamtalira Bayu Kabupaten Aceh Utara - Muhibuddin M; Nasrianti N; Zul Akli; Zainal Abidin; Fatahillah F; Johari J; Husni H (Yayasan Daarul Huda Kruengmane, 2023)
The 1945 Constitution of the Republic of Indonesia states that a good and healthy environment is a human right and a constitutional right for every Indonesian citizen. Therefore, the state, government and all stakeholders are obliged to protect and manage the environment in the implementation of sustainable development so that Indonesia's environment can remain a source and support for life for the Indonesian people and living things other. This community service is carried out using socialization methods, lectures, discussions, question and answer and practice of field crops as well as legal counseling on the Importance of Learning to Protect and Preserve the Environment for Students of State Elementary School 7 Syamtalira Bayu, North Aceh District. The result of this counseling is that students know how to practice planting plants and cleaning their school environment, there is an increase in student awareness of the cleanliness of the surrounding environment. The enthusiasm of the children to participate and care for the environment in protecting plants, plants and living things around them.